Efek dari Pemberitaan CCTV Lalu Lintas Terhadap Sikap Disiplin Berlalu Lintas - Redi Panuju; Shintya Oktaviany Aury (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Abstract Dishub Surabaya and traffic Unit Polrestabes Surabaya partners do speeding tickets through CCTV to reduce traffic violations in traffic and prevent accidents frequently happened. For the socialization of the press role is required so that residents will know this new traffic regulation. The way of the spread CCTV by the way to traffic gridlock around the continuously to be done in make the community become disciplined in the traffic signs and regulations. The underlying theory is a theory of mass communication, theory of hypodermic needle theory, S-O-R theory, discipline theory, theories of adolescence. The methodology that was used this research is quantitative methods with type of correlational quantitative. In this research that are samples are teenagers klampis semalang 96 respondents. From the results of statistics done shows that significantly is the cctv news traffic to discipline attitude traffic in teenagers Klampis Semalang Urban village Klampis Ngasem in Sukolilo Surabaya city. Keywords : news, cctv traffic, discipline traffic